Comparison of digital loudspeaker - equalization techniques - Dziechciński, P. (Archives of Acoustics, 2005)
An overview of digital equalization techniques for loudspeaker systems is presented. The known algorithms are systematized and modified. Equalization is effected by a single digital filter for the on-axis loudspeaker response. Besides classical FIR and IIR digital filter structures, their warped versions (WFIR and WIIR) are used to build equalization systems. Equalizers of different types are compared with regard to efficiency. Also information about objective and listening-test assessments of the quality of equalization obtained by the different equalizers is provided. Besides the equalizer quality assessment techniques know from the literature, new techniques, which better represent the properties of the human auditory system, are proposed. For the new techniques better agreement between the objective results and the listening-test ratings was obtained. On the basis of objective assessments of 32 equalization systems carried out for two stereophonic pairs of loudspeaker systems algorithms yielding the best results for each of the tested filter structures (FIR, IIR, WFIR and WIIR) were selected and evaluated by listening tests. Key words: equalizer, digital filter, loudspeaker system.